Kajian Drainase Pemukiman Jl. Banten Kecamatan Seberang lu II Kota Palembang dengan Program EPA SWMM 5.2 - Mozad Syahrul Ramadhan; Robi Sahbar; Pujiono T (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Palembang City, as one of the rapidly developing metropolitan areas, is facing serious problem reated to floding, primary caused by an inadequate urban drainage system. This issue is also evident in the residential area of JL. Banten Seberang Ulu 2District, Palembang City. This study aims to indety lockations with significant flood overflow in the area using the Strom Water Management Model (SWMM) software and to analyze the contributing factors to the food event.Based on a hydrological analysis with a five-year return period and simulations using SWMM version 5.2, it was found that flooding occurred at several location. For example, in Channel C1, at 01:30:00, the capacity of 0.45 m3, meaning the channel had not yet overflowed. However, by 01:45:00, the channel began to overflow, with a runoff volume of 20.30 m3 dan a capcity of only 0.87 m3. Several factors contributing to the floding include high sediment accumulation waste buildup, and poor maintenance of the drainage channels in the area.